Heat transfer in compact cross-flow mini heat exchanger - Prończuk Mateusz; Pabiś Aleksander (Polish Journal of Chemical Technology, 2023)
This paper presents the results of an analysis of heat transfer in a cross-flow mini heat exchanger (CFMHE). The purpose of the paper was to analyze the results of the experimental measurements presented in the previous work in order to determine dimensionless correlations that allow for the calculation of heat transfer coefficients for the CFMHE. Analyzed CFMHE consisted of a brass cylindrical core, in which 2 mm circular holes were drilled. A method based on an optimization procedure was used to determine the correlations describing the heat transfer coefficients, allowing the correlations to be determined without the need of measuring the mini channel wall temperature. Overall heat transfer coefficients calculated using the proposed correlations typically did not deviate by more than ±10% from the corresponding experimental results, which was a significant improvement in the quality of the fit compared to the results presented in previous work.